"Refugees from practice"? Exploring why some vets move from the clinic to the laboratory. (12th August 2021) - Anderson, Alistair; Hobson‐West, Pru
Abstract: Background: Named veterinary surgeons (NVSs) are a mandated presence in licensed animal research establishments in the UK. Some NVSs come into their laboratory roles having left general veterinary practice, which is currently facing significant recruitment and retention challenges. Understanding the factors that motivate veterinary professionals to move from practice to laboratory roles provides insight into the issues underlying recruitment and retention challenges in veterinary practice. Methods: Qualitative semi‐structured interviews with 33 NVSs were conducted in‐person or over the telephone. The interviews were transcribed, anonymised and analysed using an inductive approach. Results: Participants' accounts of their career trajectories generally emphasised push factors motivating them to leave practice, rather than pull factors to move into a laboratory role: Indeed, many participants recalled originally having little knowledge of the NVS role upon discovering it. The push factors recounted by interviewees strongly reflect the factors identified in recent research into recruitment and retention in the veterinary profession, such as business concerns and poor work‐life balance. Conclusion: This study shows that laboratory animal work is often considered by NVSs as more manageable or fulfilling than practice work. To improve retention, the push factors identified by NVSs should be addressed in practice management and veterinary pedagogy.